2018
DOI: 10.7759/cureus.2647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tilt-correction of Anteversion on Anteroposterior Pelvic Radiographs in Total Hip Arthroplasty

Abstract: Despite inaccuracies due to artifact and variations in patient positioning, anteroposterior (AP) radiographs remain the clinical standard for post-operative evaluation of component placement following total hip arthroplasty (THA). However, cup position, specifically anteversion, can be significantly affected by variations in patient positioning on an X-ray. A major cause of such artifact is unaccounted for pelvic tilt. Several methods for correcting the effects of pelvic tilt on radiographic anteversion have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Various methods of evaluating and correcting pelvic tilt on radiographs have been proposed [3,[16][17][18]; however, none have proven accurate and reliable. Some proposed methods have been found to be inappropriate for a THA population [19] while others require additional data or imaging such as standing lateral radiographs [20], which are not common practice following THA. Currently, there is a lack of consensus regarding a widely accepted and clinically validated method of tilt correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods of evaluating and correcting pelvic tilt on radiographs have been proposed [3,[16][17][18]; however, none have proven accurate and reliable. Some proposed methods have been found to be inappropriate for a THA population [19] while others require additional data or imaging such as standing lateral radiographs [20], which are not common practice following THA. Currently, there is a lack of consensus regarding a widely accepted and clinically validated method of tilt correction.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to develop a method for correcting for pelvic malpositioning on radiographs, with limited success [3,6,10,26]. We previously evaluated the ability of one commonly cited correction method [3] and found that it was unable to accurately estimate tilt in a population of patients undergoing THA [19]. The authors of that study used a younger patient population and evaluated several methods for estimating tilt.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the primary observer's measurements will be assessed by calculating the SE of measurement and Bland-Altman limits of agreement. 12 Repeat measurements will be conducted at a minimum of 2 weeks or more after the first measurement, 13 with the primary observer blinded from the initial measurement values. Interrater reliability will be determined by a second independent observer measuring the same repeated cases.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the primary observer's measurements will be assessed by calculating the standard error of measurement and Bland-Altman limits of agreement [12] . Repeat measurements will be conducted at a minimum of 2 weeks or more after the first measurement [13] , with the primary observer blinded from the initial measurement values. Inter-rater reliability will be determined by a second independent observer measuring the same repeated cases.…”
Section: Discussionmentioning
confidence: 99%